Between Work and Family: Multiple Role Strategies of Career Women in Sultan Agung Islamic University - Feria Tamara; Muchamad Coirun Nizar; M. Noviani Ardi (AL-HUKAMA: The Indonesian Journal of Islamic Family Law, 2023)
Career women have their own challenges to manage interests between work and family. However, not all career women are able to answer the demands to execute these two interests optimally. This paper aims to see what is behind the dual role of career women at Sultan Agung Islamic University and how they negotiate these two interests. This study is an empirical study using a gender approach. This paper finds that the dominant factors that place them in a dual role are economics and self-existence. Therefore, the negotiation process by establishing communication and cooperation in the household is the main thing. This strategy has an important impact on how the power of mutual trust and an attitude of responsibility is built in husband and wife relationships. In this position, the dual role chosen by career women does not further corner her position as a woman, but instead strengthens her position as the key holder of harmonious and stable relationships in the household.